Zdania inicjalne w powieściach Marka Krajewskiego - Ruszkowski, Marek (Stylistyka, 2020)
Opening sentences raise a lot of interest of both linguists and common Polish speakers. It is evident from numerous websites in which Internet users share their observations on the best opening sentences of books (most often novels), as well as theoretical papers and writing guides. The analysis of opening sentences of ten novels by Marek Krajewski (co-author of two of them being Mariusz Czubaj) is to provide an answer to the question to what extent the utterance opening of the texts of the Wroc³aw-based prose writer fulfill the requirements to be met by such type of constructions. It turns out that most crucial are syntactic and semantic features rather than lexical ones. The clash between theoretical assumptions and the M. Krajewski’s writing practice shows that opening sentences of his novels not always fall into classical determinants of incipient formulas. It also illustrates the thesis that a skillful writer does not need to cling to theoretical assumptions to create good opening sentences and novels translated into nearly twenty languages.